If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(-6 + -6x) = 198 (-6 * 3 + -6x * 3) = 198 (-18 + -18x) = 198 Solving -18 + -18x = 198 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '18' to each side of the equation. -18 + 18 + -18x = 198 + 18 Combine like terms: -18 + 18 = 0 0 + -18x = 198 + 18 -18x = 198 + 18 Combine like terms: 198 + 18 = 216 -18x = 216 Divide each side by '-18'. x = -12 Simplifying x = -12
| 1/4*9= | | -42=7k | | (x^4/9)^2 | | 3(3+6x)=129 | | 1.5=3 | | 5+7(8r-2)=0 | | .25x+5=.75x+2 | | y=19x+2500 | | 5m+31=9m-2 | | 9-1y=4 | | -5(3+6x)=-15 | | (x-1)+5=230 | | =48+25 | | 5c-2a=1 | | 15.(-2/3) | | 10=-2+n | | x^2-8x+23=f(x) | | 4a+3b=17 | | 5(2+1)=45 | | 2x^2a+2xa^2= | | 2(11+3n)=23 | | B+10=50 | | 8y-5=51 | | logx-3logy=4 | | Z+8=35 | | 4f+10=2f+22 | | tan(51)=x/8 | | 65x=20 | | 9.6/z=-3.2 | | (X+4)(x-2)=40 | | 5g+(-7)=-52 | | xa+5x-4=10 |